Dynamic Analysis of Offshore Structures with the Effect of Soil-Structure Interaction - Ali, Anis A. Mohamad; Essa, Mohamad J. K.; Saleh, Samoel M.; Saleh, Samoel M.; Ali, Anis A. Mohamad; Essa, Mohamad J. K. (Basrah Journal for Engineering Sciences, 2006)
In the present study, the dynamic analysis of jacket type offshore structures under the action of sea waves is carried out. The finite element method is adopted for the solution of the problem. The effect of soil-structure interaction on the dynamic behavior of the offshore structure is taken into account due to the deformations of the soil caused by the motion of the structure, which in turn modify the response of the structure. The supporting elastic foundation is represented by Winkler type model having normal and tangential moduli of subgrade reaction. These moduli may be constant or varying linearly or nonlinearly along the embedded length of the piles that support the offshore structure. The pile tip conditions are also considered. A time domain solution is recommended. The generalized Morison’s equation is used to calculate the wave forces and Airy’s linear theory to describe the flow characteristics. Both free and forced vibration analyses are studied. The dynamic response has been obtained by modal analysis in conjunction with Wilson-0 method. As an example, a modified model of an actual jacket type offshore platform is analyzed under the action of wave forces.